Scenarios for entrepreneurship: the experience of two Higher Education Institutions in Medellín (GEON Journal (Management, Organizations and Business), 2026)
Problem: Inadequate management of social entrepreneurship and innovation within Higher Education Institutions (HEIs) limits the fulfillment of their foundational objectives and the generation of social value. Objective: This study aimed to identify the characteristics of entrepreneurial students at two HEIs in Medellín and assess the management of the entrepreneurship process within these institutions. Materials and Methods: A descriptive, cross-sectional study was conducted with a sample of 662 entrepreneurial students from two educational institutions in Medellín. Data was collected using a digitally administered instrument, validated by three experts, gathering information on sociodemographics, entrepreneurial intentions and projections, characteristics of ongoing ventures, and students' engagement with HEIs' entrepreneurship departments. Results: Student characteristics were diverse, and institutions showed variability in their support processes. Findings highlight the importance of aligning entrepreneurship and innovation departments with student needs, fostering an entrepreneurial ecosystem, and strengthening institutional capacities. Discussion: Integrating entrepreneurship and innovation categories into educational policies at all levels enables HEIs to respond to societal demands for human development and capacity building in local territories, positioning universities as key actors. Conclusions: Adapting entrepreneurship departments is crucial for comprehensively, efficiently, and coherently supporting student initiatives to meet current challenges and dynamics. Contribution/Originality: This study provides empirical evidence on the characteristics to consider for supporting students through institutional entrepreneurship management.
Keywords: Entrepreneurship; Innovation; Higher education; Vocational training; Economic and social development; Education and development